Brain Interconnections - Duenas, Alejandro; Rosas, Juan Carlos Aldaz; Hernandez, Francisco Jimenez; Caloca, M. M. A. Ortiz (JOURNAL OF ADVANCES IN PHYSICS, 2015)
The interaction brain-machine is now an indissoluble fact. The repercussions this fact will have in future are presently unimaginable. As mentioned in [1] the nerve axon can now be modeled by a cable or a planar high speed interconnection, no matter what kind of interconnection will be used.Â  The brain development is clearly shown in a stupendous book of the SOCIETY FOR NEUROSCIENCE treating the brain and the nervous system. An extraction of the brain development chapter is here included to show the relationship among the physiological brain connections [2] and the high speed electrical connections [1]. On the other hand, because of the massive volume of information storage now a day the synchronization clock speeds are all in the range of GHz almost reaching the THz. At these very high frequencies the behavior of the interconnects are more like that of a transmission line, and hence distortion, delay, and phase shift-effects caused by phenomena like cross talk, ringing, and overshoot are present and may be undesirable for the performance of a circuit or system. Thus, the interconnects do not have to be considered like simple conductors or lumped elements. All this gives rise to a new emerging discipline known as signal integrity. This discipline is extremely important to maintain the signal quality on microstrip circuits [3]. In this discipline the correct timing and signal quality preservation preventing transients and false switching are studied in order to avoid excessive delays.